Smart Farming Equipment Rental System - S. Suganth,; Dr. K. Santhi, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Agriculture is a labour-intensive sector, requiring a lot of machinery for agriculture. These machines are able to finish tasks in agriculture considerably quicker. The various types of machinery used in agriculture include tractors, harvesting tools, tillage tools and other farming equipment. However, these machineries and tools are priced very expensive and are not affordable by all farmers. The high purchase and maintenance cost leads to high demand for renting these machineries. The Smart Farm Equipment Rental Platform is an innovative approach to address the challenges faced by small and medium scale farmers. By providing a systematic and reachable system for renting high-cost farming equipment or machineries, the platform breaks the gap between farmers and equipment owners. It enables efficient resource utilization, reduces costs and helps in promoting sustainable agricultural practices. Equipment owners will also be able to utilise their resource instead of keeping the resources unutilised. This platform also helps the farmers that invested a huge amount on this equipment to utilise their resource and generate an additional income. This platform helps farmers to rent equipment and cut the additional expenses.
Keywords: Machinery; Systematic; Sustainable; Agriculture